Les centralités spécialisées des sports de nature : hauts lieux et modestes pôles touristiques - Valérian Geffroy (Revue de Géographie Alpine)
The article introduces the notion of “specialised centrality” to denote places where tourist activity is based on a specific activity – outdoor sports in the case under study here. This notion offers a complement to territorial models of tourism, as it identifies small clusters that do not fit into either the category of tourist resorts or that of dispersed tourism. The notion takes into account both the spatial characteristics of these places and the way in which they are practised. This paper is based on field research carried out in major hotspots of outdoor sport tourism, and is illustrated in particular with the case of the Haute-Durance basin.The different dimensions of specialised centralities are outlined: material qualities, symbolic values and community co-presence. Examples of particularly isolated specialised centralities are presented in order to emphasise their modest dimensions in terms of territorialisation and economic activity. However, the different ways in which specialised centralities are integrated in the tourist fabric and the territory are also evoked.The article concludes by discussing how the perspective of centralities helps to refine the understanding of the relationship between tourist practices and territorial developments, and how the study of specialised centralities consolidates the analyses of the “presential” economy of tourist territories.